Pengaruh Pelatihan dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Maju Tambak Sumur Lampung Selatan - Wahyudi Siregar; Suhroji Adha; Djaka Adiwinata (Jurnal of Management and Social Sciences, 2024)
This research aims to: (1) find out how much influence training has on employee performance; (2) to find out how much the work environment influences employee performance; (3) to find out how much training and work environment influence employee performance. This research is quantitative research and was conducted at PT Maju Tambak Sumur Lampung Selatan with a total of 65 respondents using purposive sampling techniques. The data in this research was taken using questionnaires, observations, interviews. The analysis technique used to test the hypothesis is multiple linear regression analysis technique with the help of SPSS 29. From the results of this test it can be concluded that (1) the training variable (X1) has a positive effect on employee performance (Y); (2) work environment variables (X2) have a positive effect on employee performance (Y); (3) training variables (X1) work environment (X2) have a positive effect on employee performance (Y).